(untitled) (AYUSHDHARA, 2017)
The human skin is the outermost covering of the body and largest organ of the integumentary system. Diseases of the skin though not fatal but it scars the confidence of the individual. Therefore there is rise in incidence of dermatolgical cases in general practise. But to treat a disease it is of utmost importance to have proper knowledge of the affected organ. The present review article encompasses the concept of skin i.e., Twacha in Ayurveda including its Nirukti (etymology), Sharirrachana (anatomy), Sharirkriya (physiology), Vikriti (pathology) described by different Acharyas with modern insights on relevant topics. Apart from this unique concept of Ayurveda regarding Varna, Chhaya and Prabha and Twaksara are also mentioned. Hence one of the important karma of Twak is to act as a strong physical barrier against microbial invasion and protect the body against mechanical, thermal, chemical, osmotic and photo damage.